Integrated Behavioral Practices among Mothers of Stunted Children in a River Basin Community - Marlenywati Marlenywati; Indah Budiastutik; Elly Trisnawati; Ayu Rizky; Winda Mulia Ningsih (MEDICA (International Medical Scientific Journal), 2026)
Stunting remains a significant public health challenge, particularly in vulnerable communities such as urban riverine settlements. This study aimed to evaluate changes in key behavioral practices following the implementation of an integrated behavioral intervention among mothers of stunted children under five in the Kapuas River Basin community of Pontianak. This study employed a one-group pretest–posttest quasi-experimental design involving 30 mothers of stunted children. The intervention consisted of modules on household hygiene practices, responsive caregiving, and active feeding practices, delivered through direct facilitation by trained health workers at Posyandu (integrated health service posts). Data were analyzed using paired sample t-tests to assess differences before and after the intervention. The findings demonstrated significant improvements across all three behavioral domains. Household hygiene practices improved with a moderate effect size, indicating better hygiene behaviors at the household level. The greatest improvement was observed in responsive caregiving, with a large effect size reflecting enhanced caregiver child interactions following the intervention. Active feeding practices also showed improvement, although with a small-to-moderate effect size, suggesting that changes in feeding behavior may require more intensive and sustained support. In conclusion, community-based integrated behavioral interventions are effective in improving caregiving and hygiene practices associated with stunting risk pathways in urban riverine communities. These findings highlight the importance of context-specific behavioral strategies as part of comprehensive, community-based stunting prevention efforts in high-risk environments.